2023
DOI: 10.1111/bjet.13306
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of video and stereoscopic 360° virtual reality‐supported instruction in high school biology courses

Abstract: The promise of using immersive technologies in learning has increasingly been attracting researchers' and practitioners' attention. However, relevant empirical works are usually conducted in fully controlled Virtual Reality (VR) laboratories, as opposed to conventional settings. This quasi-experimental study compares the effectiveness of video learning resources to that of stereoscopic 360° VR, as supplements to the traditional instructional approach. The potential of such methods was examined in high school s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…2019) evidenció que la permanencia de los logros de aprendizaje alcanzados fue disminuyendo en el tiempo. Como lo indican Bai (2022),y Christopoulos et al (2023), existe la necesidad de continuar investigando y perfeccionando el uso de las diferentes TD debido a su constante evolución. En este sentido, la implementación de las TD para generar un cambio significativo en el rendimiento académico, aumentar el nivel de conocimiento y disminuir la carga cognitiva, requieren de di-dácticas y pedagogías propias para este tipo de metodologías de enseñanza aprendizaje y no integrar tecnologías nuevas a estrategias tradicionales (Amores-Valencia et al, 2023).…”
Section: Resultados Y Discusiónunclassified
“…2019) evidenció que la permanencia de los logros de aprendizaje alcanzados fue disminuyendo en el tiempo. Como lo indican Bai (2022),y Christopoulos et al (2023), existe la necesidad de continuar investigando y perfeccionando el uso de las diferentes TD debido a su constante evolución. En este sentido, la implementación de las TD para generar un cambio significativo en el rendimiento académico, aumentar el nivel de conocimiento y disminuir la carga cognitiva, requieren de di-dácticas y pedagogías propias para este tipo de metodologías de enseñanza aprendizaje y no integrar tecnologías nuevas a estrategias tradicionales (Amores-Valencia et al, 2023).…”
Section: Resultados Y Discusiónunclassified
“…Utilizing VR technology, educators can create learning experiences tailored to students' needs and preferences, maximizing their understanding and interest in the subject matter (Christopolous and Nikolaos, 2023). This relates to research (Maloy et al, 2019), which suggests that actively engaged students can succeed in overcoming lesson challenges, which can help increase students' cognitive motivation.…”
Section: Application Of Virtual Reality Media In Improving Student Mo...mentioning
confidence: 99%
“…Studies integrating VR with GBL found significant improvement in students’ learning motivation, positive learning experiences ( Christopoulos et al, 2023 ) and learning outcomes, such as learners’ ability in recall processes, as well as enhancement of their cognitive thinking and problem-solving abilities (Shi et al, 2019). Previous studies have shown clear advantages of VR across different STEM fields in terms of students’ positive attitudes, engagement, and performance (for a review see Pellas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%